RISK FACTORS OF ABDOMINAL WOUND DEHISCENCE: EVALUATION AND OUTCOME (Iraqi Journal of Medical Sciences, 2016)
Background:Wound Dehiscence is the premature opening of a wound along surgical suture. It is a surgical complication that results from poor wound healing that can increase significantly the risk of morbidity and mortality. Risk factors in general are age, diabetes, obesity, cancers, emergency surgery, pulmonary diseases, malnutrition, weight loss, anemia, chemotherapy and radiotherapy.Objective:To identify the most important risk factors for wound dehiscence in an attempt to decrease the incidence, morbidity and mortality of wound dehiscence.Methods:This is a cross sectional study with convenient sample of 66 patients 48 males and 18 females with wound dehiscence after laparotomy in Al-Kindy Teaching Hospital, Baghdad, Iraq from February 2008 to May 2011. The medical records for all patients regarding risk factors responsible for delayed wound healing and burst abdomen of all patients were reviewed. Laparotomy done for all patients under general anesthesia. Retention through and through sutures inserted on both sides of the abdominal wall were used in all cases.Results:The commonest time for the wound to burst was on the 10th postoperative day. The average duration of hospital staying was 26 days. The most common primary diagnosis of those patients was intestinal obstruction (30.3%), and adhesolysis was the most common operative procedure (18.2%). Emergency laparotomy was the most frequent factor found (92.4%). The mortality rate in patients with wound dehiscence increased with an increment of the number of risk factors, it was 15.6% in Patients who had 2-4 risk factors and reached 100% for patients with 8 risk factors.Conclusion:The identification of the avoidable factors and their correction could reduce the risk of development postoperative burst abdomen and in turn decrease the mortality and morbidity rate.Keywords:Wound dehiscence, risk factors, laparotomy
Keywords: Wound dehiscence; risk factors; laparotomy